The Effect Of Workload, Job Satisfaction, And Organizational Support On Auditor Performance With Psychological Well-Being Mediation (Study At The Inspectorate General Of The Ministry Of Manpower) - Hastuti, Nur Widi; Kanto, Dwi Sunu (SEAN Institute, 2024)
This study aims to analyze the effect of workload, job satisfaction, and organizational support on auditor performance with psychological well-being mediation in the Inspectorate General of the Ministry of Manpower. This study was conducted because of the complexity of auditor work, variations in job satisfaction, the importance of organizational support that can impact auditor performance in government environments, and psychological well-being that is often ignored by some people. The approach used in this study is path analysis with the Partial Least Squares (PLS) method. The results of the study indicate that workload and job satisfaction do not affect auditor performance and psychological well-being, while organizational support affects auditor performance and psychological well-being. And psychological well-being affects auditor performance. In addition, psychological well-being is proven to mediate the relationship between organizational support and auditor performance, but does not mediate the relationship between workload and job satisfaction with auditors. This study provides important insights for improving auditor performance through effective workload management, increasing job satisfaction, strengthening organizational support, and attention to psychological well-being.